2023
DOI: 10.3390/ijms24098315
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Novel Active Layer-by-Layer Edible Coating on the Qualitative and Biochemical Traits of Minimally Processed ‘Annurca Rossa del Sud’ Apple Fruit

Abstract: The color changes brought on by the enzymatic interactions of phenolic compounds with released endogenous polyphenol oxidase and the penetration of oxygen into the tissue has a significant impact on the commercialization of fresh-cut fruit, such as apples. This process causes a loss of quality in fresh-cut apples, resulting in browning of the fruit surface. By acting as a semipermeable barrier to gases and water vapor and thus lowering respiration, enzymatic browning, and water loss, edible coatings can provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…This study showed that in the uncoated fresh-cut samples, there was a significant increase in H 2 O 2 levels of about 17.6% compared to the coated samples at the end of cold storage. Exogenous coating treatments enhance the efficiency of the ascorbate-glutathione cycle, a crucial antioxidant pathway involved in the detoxification of ROS, as demonstrated in different fresh-cut fruits such as apple [72,73], pear [74], melon [14], peach [75], and avocado [70].…”
Section: Enzymatic Antioxidant Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that in the uncoated fresh-cut samples, there was a significant increase in H 2 O 2 levels of about 17.6% compared to the coated samples at the end of cold storage. Exogenous coating treatments enhance the efficiency of the ascorbate-glutathione cycle, a crucial antioxidant pathway involved in the detoxification of ROS, as demonstrated in different fresh-cut fruits such as apple [72,73], pear [74], melon [14], peach [75], and avocado [70].…”
Section: Enzymatic Antioxidant Systemmentioning
confidence: 99%
“…Multivariate analysis represents a valuable approach to elucidate the complex interactions between postharvest treatments and storage conditions in fruits. Furthermore, these techniques have been used to identify patterns and correlations within large datasets, elucidating the impact of postharvest treatments on fruit metabolism and quality attributes [72,74,76].…”
Section: Multivariate Data Analysismentioning
confidence: 99%
“…[15][16][17][18] SA is a "Generally Recognised as Safe" (GRAS) raw material, oen used as a stabiliser and thickener in the food industry. 19 CMC is a negatively charged cellulose derivative derived from natural cellulose. [20][21][22] It is soluble in water, has excellent biocompatibility and good viscosity, is stable to light and heat, is non-toxic and non-allergenic, and is ordinarily prepared as a substrate for active packaging.…”
Section: Introductionmentioning
confidence: 99%